The effect of condensate water on the performance of automotive air conditioning system under difference evaporator air inlet temperature - Mohamad Firdaus, Sukri (Universiti Malaysia Perlis (UniMAP), 2020)
Link to publisher's homepage at http://ijneam.unimap.edu.my